Implementasi Kebijakan Dana Desa Terhadap Efektivitas Anggaran Desa Dalam Pemberdayaan Ekonomi Masyarakat di Masa Pandemi Covid-19 (Study Kasus Pada Desa Tajinan Kecamatan Tajinan Kebupaten Malang) - Dewi Sabrina Aisyah Putri; M. Ridwan Basalamah; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study was to determine the analysis of the implementation of the village fund policy on the effectiveness of the village budget in empowering the community's economy during the covid-19 pandemic. The data analysis method used is descriptive qualitative analysis with village head informants and village officials. The results of this study indicate that the implementation of the village fund policy in the Tajinan village during the Covid-19 period went quite smoothly. And the effectiveness of the village fund budget in empowering the community's economy during the COVID-19 pandemic in Tajinan village is quite effective. The realization of the village budget in 2019 to 2020 has changed. Community empowerment funds in 2019 were used to improve health facilities and infrastructure in the Tajinan village. Community empowerment funds in 2020 were diverted for disaster management and emergency funds. In accordance with Ministerial Regulation No. 8 of 2020 regarding Covid-19 response villages and the confirmation of the Village Cash Intensive Work. Based on the calculation of the effectiveness ratio, it appears that the village fund budget allocated for the handling and prevention of COVID-19 has been effective. The community in Tajinan Village was given socialization about the COVID-19 pandemic. And the village has also created a new program, namely a resilient village so that the community remains stable and awake despite the COVID-19 pandemic.Keywords: village fund policy, village budget effectiveness, community economic empowerment, covid-19